Service Oriented Integration of Distributed Heterogeneous IT Systems in Production Engineering Using Information Standards and Linked Data. (19th March 2017) - Zadeh, Navid Shariat; Lindberg, Lars; El-Khoury, Jad; Sivard, Gunilla
Abstract : While design of production systems based on digital models brings benefits, the communication of models comes with challenges since models typically reside in a heterogeneous IT environment using different syntax and semantics. Coping with heterogeneity requires a smart integration strategy. One main paradigm to integrate data and IT systems is to deploy information standards. In particular, ISO 10303 STEP has been endorsed as a suitable standard to exchange a wide variety of product manufacturing data. One the other hand, service-oriented tool integration solutions are progressively adopted for the integration of data and IT-tools, especially with the emergence of Open Services for Lifecycle Collaboration whose focus is on the linking of data from heterogeneous software tools. In practice, there should be a combination of these approaches to facilitate the integration process. Hence, the aim of this paper is to investigate the applications of the approaches and the principles behind them and try to find criteria for where to use which approach. In addition, we explore the synergy between them and consequently suggest an approach based on combination of them. In addition, a systematic approach is suggested to identify required level of integrations and their corresponding approaches exemplified in a typical IT system architecture in Production Engineering.